SISTEM APLIKASI PEMBELAJARAN BANGUN RUANG UNTUK SEKOLAH DASAR - Sudewi, Sudewi; Irviani, Rita; Kristina, Marilin (STIT Pringsewu, 2016)
The purpose of this research is to improve learning activities using props Build Space models for the elementary school, describing the process of design of interactive multimedia on the subjects of Mathematics, knowing the results of the validation of interactive multimedia. The problem in this research is the students' grades in Maths low, conventional learning, and interactive multimedia that support the mathematics is not yet available. Development steps include: analysis, design, development, implementation, and evaluation. Subject trials, the master of the course content, instructional design experts, media expert learning, small group evaluation, individual evaluation, and field evaluation. Data collection techniques are questionnaires to data from expert reviews and test students. Data were analyzed by using a Research and Development (R & D). The results showed the process of interactive multimedia design. The results of research that application of the model geometry aids in Mathematics Learning can increase physical activity can improve mental activity, can improve students' emotional and can improve student learning outcomes.